2010
DOI: 10.4049/jimmunol.1000892
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Role for C5L2 in the Pathogenesis of Experimental Allergic Asthma

Abstract: Material Supplementary 2.DC1http://www.jimmunol.org/content/suppl/2010/10/25/jimmunol.100089References

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
89
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(94 citation statements)
references
References 54 publications
5
89
0
Order By: Relevance
“…1 In addition to C5aR, C5a can also interact with a second receptor, C5L2, which controls the development of Th1 and Th17 cells in experimental allergic asthma at the DC/T cell interface and promotes Th2 immune responses independent of pulmonary DCs. 36 This effect may become dominant in vivo in the absence of C5aR. Finally, C5aR signaling in BMDCs may inappropriately reflect C5aR-mediated regulation of the distinct pulmonary DC subsets in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…1 In addition to C5aR, C5a can also interact with a second receptor, C5L2, which controls the development of Th1 and Th17 cells in experimental allergic asthma at the DC/T cell interface and promotes Th2 immune responses independent of pulmonary DCs. 36 This effect may become dominant in vivo in the absence of C5aR. Finally, C5aR signaling in BMDCs may inappropriately reflect C5aR-mediated regulation of the distinct pulmonary DC subsets in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…OVA-sensitized C5L2-deficient mice exhibit reduced AHR, inflammatory cell infiltration, and airway inflammation (Chen et al, 2007). Similarly, HDM-sensitized C5L2-deficient mice show significantly attenuated AHR and airway inflammation that is associated with decreased mucus production, Th2 cytokine production, and serum IgE levels (Zhang et al, 2010), confirming the pro-inflammatory role of C5L2 in the development of asthma. The available data further indicates that C5L2 also has a regulatory impact on mDCs.…”
Section: Allergic Inflammation: Allergic Asthmamentioning
confidence: 68%
“…Taken together this suggests that C5a/C5aR complex controls IL-17A by limiting IL-23 production (Lajoie et al, 2010). As described above, Th17 development in experimental asthma is not only regulated by C5aR but by C5L2 as well (Zhang et al 2010). In addition to its impact on Th17 cells, C5a may also regulate the development of T regs (Palomares et al, 2010).…”
Section: Allergic Inflammation: Allergic Asthmamentioning
confidence: 69%
See 1 more Smart Citation
“…Owing in part to the previously enigmatic functions of C5aR2, and a predominant focus on C5aR1, the potential for C5aR2 to be targeted therapeutically remains largely unexplored. To date, animal knockout studies have demonstrated an effect of C5aR2 modulation in spinal injury, allergic asthma, and sepsis (Biggins et al 2017;Rittirsch et al 2008;Zhang et al 2010;Li et al 2013). …”
Section: Targeting Of C5ar2mentioning
confidence: 99%